2008
DOI: 10.1080/07362990802286418
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Weak Disorder for Lévy Directed Polymers in Random Environment

Abstract: We consider Lévy directed polymers in the Poisson random environment. We give conditions for strong or weak disorder in terms of the Lévy exponent of symmetric Lévy process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Indeed, one might consider the model in which the random walk S is not the simple symmetric random walk on Z d , but belongs to the domain of attraction of an α-stable law with α ∈ (0, 2], see [12]. Let us consider the case of the dimension 1 + 1: it has been showed that weak disorder holds for β small enough when α ∈ (0, 1), see [12], and that strong disorder holds for any β > 0 when α ∈ (1, 2), see [25] (in a continuous setting). A similar question has been studied in [7], where a disordered scaling limit can be constructed whenever α ∈ (1,2].…”
Section: Main Resultmentioning
confidence: 99%
“…Indeed, one might consider the model in which the random walk S is not the simple symmetric random walk on Z d , but belongs to the domain of attraction of an α-stable law with α ∈ (0, 2], see [12]. Let us consider the case of the dimension 1 + 1: it has been showed that weak disorder holds for β small enough when α ∈ (0, 1), see [12], and that strong disorder holds for any β > 0 when α ∈ (1, 2), see [25] (in a continuous setting). A similar question has been studied in [7], where a disordered scaling limit can be constructed whenever α ∈ (1,2].…”
Section: Main Resultmentioning
confidence: 99%
“…In [44], a continuous version of α-stable longrange polymers is considered. Specifically, a phase transition was shown for the normalized partition function associated to a Lévy process subjected to a Poissonian random environment.…”
Section: Continuous Versions Of Long-range Polymersmentioning
confidence: 99%
“…Most of the literature concerning the study of directed polymers associates it with a simple symmetric random walk [8,6,7,15] or when the distribution of the increments belongs to the domain of attraction of an α-stable law for some α ∈ (0, 2] [11,18,25].…”
Section: Introductionmentioning
confidence: 99%